W/O high internal phase emulsions (HIPEs) stabilized by a piperazinyl based emulsifier. Issue 43 (1st November 2021) - Jiang, Feng; Gao, Donghui; Feng, Xi; Pan, Jiaming; Pu, Wanfen
Abstract : In this study, a piperazinyl-based emulsifier (EA/AMPA) was synthesized to prepare water-in-oil (W/O) high internal phase emulsions (HIPEs). Abstract : In this study, a piperazinyl-based emulsifier (EA/AMPA) was synthesized to prepare water-in-oil (W/O) high internal phase emulsions (HIPEs). Using kerosene as the oil phase, stable HIPEs with internal phase fractions of up to 98% were prepared. This enabled the EA/AMPA to have a high efficiency, as the HIPEs with a 90% internal phase fraction could be easily prepared with 0.1% of EA/AMPA. In addition, the formation of HIPEs was not affected by the addition of Na + . Because of the fact that EA/AMPA has a hydrophilic head with two tertiary amines, EA/AMPA could be easily recovered from the oil phase by adjusting the pH to acidic values. Moreover, the unique structure promoted the formation of stable HIPEs, even with crude oil used as the oil phase. The results indicate that EA/AMPA has the potential to significantly contribute to the preparation of W/O HIPEs and that the design of the hydrophilic head with two tertiary amines can provide a reference for the fabrication of new W/O emulsifiers.